Konsep dan Penerapan Ujrah Al-Mitsli Menurut Perspektif Ekonomi Islam - Habibatu Zahro, Efa; Hanifuddin, Iza (Jurnal Dinamika Ekonomi dan Bisnis, 2024)
In determining Al-Ujrah (wages) amount in Indonesia, the current approach focuses on meeting the minimum physical requirements rather than ensuring a satisfactory standard of living based on fundamental human needs. In the context of Islamic beliefs, Afzalurrahman had addresses similar topics as mentioned in this research. In reality, the disparity in wage representation remains far from the desired equality set by Indonesian law. According to Islahi's reference to Ibn Taimiyah, fair or equal wages are wages that are determined solely by market demand and supply factors, without any involvement from the government. Economists and Islamic economic thinkers view wages as a crucial concept in economic activities. In this situation, the primary emphasis is on the principles of fairness in providing Al-Ujrah, as elaborated in the Al-Qur`an. Afzalur Rahman advocates for the idea of Ujrah Al-Mitsli, highlighting the significance of offering fair wages that uphold principles of justice rather than exploiting workers. The research employed a literature review using a qualitative method. The findings of this study support what was stated by religious figures in Al-Islah who advocate for equal and fair wages that are determined solely by the laws of supply and demand in the market, without any interference from the governmentÂ